Principal Leadership in Strengthening Students’ Discipline - Edi Purnomo; Meilia Rosani; Darwin Effendi (Yayasan Sembilan Pemuda Indonesia, 2027)
This study examines how principal leadership strengthens student discipline at SMA Negeri 1 Sungai Lilin, Musi Banyuasin, Indonesia, within the school’s specific social and geographical context. A descriptive qualitative design was employed, collecting data from one principal, four teachers, and nine students through semi-structured interviews, non-participant observation, and document analysis. Data were reduced, organized thematically, displayed, and verified through source and technique triangulation. The principal performed interconnected roles as educator, manager, administrator, supervisor, leader, innovator, and motivator. Democratic leadership dominated, characterized by two-way communication, shared decision-making, and persuasive guidance, while situational firmness was applied for serious violations. Discipline management combined clear rules, exemplary behavior, point-based records, counseling, parental communication, CCTV monitoring, and application-based coordination. A multi-tier leadership pattern emerged wherein the principal influenced student behavior indirectly by developing teachers as consistent role models. Major constraints included weak discipline internalization, mobile-phone misuse, family supervision gaps, peer influence, geographic dispersal, and limited digital infrastructure. Responses included coordinated discipline teams, periodic evaluation, and data-informed monitoring. This study uniquely demonstrates a multi-tier, indirect leadership model for discipline management in a geographically dispersed plantation settlement context. Sustainable student discipline requires leadership integrating example, organizational consistency, technology, collaboration, and contextual flexibility. This research contributes empirical evidence that discipline is most effectively internalized as school culture through integrated leadership approaches, offering actionable insights for school leaders in similar rural Indonesian settings.